ПІДВИЩЕННЯ ЕФЕКТИВНОСТІ БУРІННЯ ПОХИЛО-СКЕРОВАНИХ СВЕРДЛОВИН ЗА РАХУНОК РОЗРОБЛЕННЯ ТА ЗАСТОСУВАННЯ ГЕНЕРАТОРІВ ГІДРОКОЛИВАНЬ - Кунцяк, Я.В.; Чернова, М.Є.; Новіков, В.Д. (Институт сверхтвердых материалов им. В. Н. Бакуля Национальной академии наук Украины, 2020)
For objective reasons, the average drilling depths in Ukraine are increasing and, at the same time, the percentage of inclined wells is increasing in the total volume of drilling. The combination of these factors causes a number of new problems. This is especially true for bringing the axial load into the bottom of deep, inclined and horizontal sections of wells. In order to eliminate these shortcomings, it is proposed to use special devices developed on the basis of hydraulic oscillators. To simplify the possibility of use, these generators are mounted and combined directly in the structures outside the standard vane calibrators and hubs. Devices according to the developed calculation scheme are placed in the arrangement of the bottom of the drill string and the drill string. The article solves the scientific and technical problem of increasing the efficiency of drilling deep inclined sections of the wellbore using methods of mathematical modeling, experimental and industrial research, the results of which are aimed at solving an important scientific and economic problem, which is to create and improve new domestic technologies , in particular, the arrangement of the bottom of the drill string and technical devices, the use of which provides: prevention of the phenomena of seizures of the drill string; improving well bottom cleaning; increasing the efficiency of bringing the dynamic axial load of the rock-destroying tool in the bottom of the well; increasing the speed of drilling in the mining and geological conditions of oil and gas fields in Ukraine. The introduction of the developed technology for drilling deep inclined sections of oil and gas wells ensures the successful construction of wells in the mining and geological conditions of Ukrainian fields, as well as the restoration of liquidated, inactive and low-flow wells. In particular, based on the method of mathematical modeling, and on the basis of studies of the influence of hydrodynamic oscillations on the dynamics of flushing fluids in the annulus and on the dynamics of BC, a series of hydraulic oscillators for working conditions in deep wells is developed. The developed mathematical model helps to calculate the influence of the parameters of the hydraulic oscillator on its performance. The use of generators of this action in the design of rock-breaking tools and in the arrangement of the bottom of the drill string for drilling conditions in deep inclined wells increases the efficiency of bringing dynamic axial load into the bottom of the well, increasing the drilling speed by 20 ÷ 35%. The article proposes a methodology for determining the places of additional placement of hydro-oscillation generators in the arrangement of the bottom of the drill string in order to prevent the phenomena of entrapment in deep inclined sections of the wellbore, as confirmed by industrial tests in Ukrainian fields. The results of the research contributed to the development of guidelines and recommendations for the application of the developed devices and technologies, the implementation of which will increase the efficiency of drilling deep inclined sections of the wellbore, reduce their commercial value, and increase Ukraine's energy independence. In contrast to the known mechanical devices, the proposed are characterized by a high value of efficiency, durability and the ability to set the required frequencies and amplitudes of oscillations. Industrial research and application of new devices and schemes of their location in the arrangement of the bottom of the drill string proved their efficiency and increase the mechanical drilling speed by an average of 20 ÷ 35%.